Financial Distress Prediction: The Ownership Structure and Management Agency Cost - Maya Indriastuti; Indri Kartika; Naila Najihah (The Indonesian Journal of Accounting Research, 2021)
This research aimed to predict the financial distress through ownership structure and management agency cost. The ownership structure was tested by managerial ownership and institutional ownership. Meanwhile, the management agency cost was tested by administrative cost ratio. The population of this research were all companies listed in Indonesia Sharia Stock Index year 2016-2018 by using purposive sampling technique. Based on the criteria that have been determined, the total samples were 129 companies. The analysis of the data in this research used logistic regression analysis. The results showed that institutional ownership has a significant negative effect towards the financial distress. Despite, the managerial ownership and management agency cost have a insignificant negative effect toward the financial distress.